NILAI-NILAI PENDIDIKAN DALAM TRADISI DAMPEANG PADA KESENIAN LUAMBEK DI NAGARI LUBUAK PANDAN LAREH ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Gusti Laraski; Marzam Marzam; Harisnal Hadi (SENDRATASIK UNP, 2018)
AbstractThis article aimed to know the education values  of the Dampeang tradition on the art of Luambek in Nagari Lubuak Pandan Lareh Enam Lingkung Kabupaten Padang Pariaman. This study was qualitative with descriptive method. Instrument in this study was the researcher and assisted by some tools such as stationery, camera and audio recorder. Technique of data collection was done by doing observation, interviews, library research and documentation.Dampeang is the art of the vocal which has connection tightly toward the art of Luambek, every motion made by Paluambek taking the plot of Dampeang. Results of this study showed that there were number of the education values of Dampeang on the art of Luambek which could be used in daily life either individually or socially. The education values of it were value of ethics education, discipline, social studies, religious education and political education. Keywords: Education, Dampeang Tradition, Art Luambek.